(untitled) (Journal of Pharmaceutical Negative Results, 2023)
One of the most popular drinks in the world, tea is a member of the family Theaceae, obtained from the plant Camellia Sinensis, found explicitly in humid and warm regions, attracts interest for its flavour and scent as well as its advantageous health properties. It is divided into three main categories: unfermented green tea and white tea, partially fermented oolong tea, and black tea that has undergone fermentation. Green tea is currently the psychostimulant most often used worldwide, as it has been shown to enhance cognitive thinking, improve neuromuscular coordination, and reduce tension and anxiety. However, it also contains caffeine members of methylxanthines which, in high amounts, more than its moderate dose, i.e., 400mg/day, can cause significant toxicity and even lethality showing symptoms such as involuntary contraction of the muscles, failure of the respiration, and heart, coma, migraine, or even death of the person in adverse cases. This study’s objective is to determine the qualitative content of caffeine released in green tea after boiling over time. Liquid chromatography is used for the detection of caffeine. To establish a more exact relation between the amounts of caffeine taken and its physiological effects, it is crucial to create more accurate, easy, and quick procedures for the detection of caffeine. Caffeine was successfully eluted using this technique in three minutes, with a few additional peaks. The standard calibration curve showed exemplary linearity, and the correlation coefficient was above 0.9983.